Hypoxia increases the proliferation of brain capillary endothelial cells via upregulation of TMEM16A Ca2+-activated Cl− channels - Takahisa Suzuki; Yoshiaki Suzuki; Kiyofumi Asai; Yuji Imaizumi; Hisao Yamamura (Elsevier, 2021)
The blood-brain barrier (BBB) is mainly formed by brain capillary endothelial cells (BCECs) and is exposed to hypoxic environments under pathological conditions. The effects of hypoxia on the expression and activity of Ca2+-activated Cl− (ClCa) channels, TMEM16A, were examined in bovine brain endothelial t-BBEC117 cells and mouse BCECs. The expression of TMEM16A was upregulated by hypoxia. Whole-cell ClCa currents increased under hypoxia. Hypoxia also increased cell proliferation and trans-endothelial permeability, which were attenuated by ClCa channel blockers or TMEM16A siRNA. These findings are useful for elucidating the pathological role of TMEM16A ClCa channels in the BBB during cerebral ischemia.